CHARACTERISTICS OF THE CONSTITUTION OF ANTI-INFECTION RESISTANCE OF KORAKUL SHEEP (Academia Science Repository, 2023)
The natural immunobiological features of Karakul sheep of different constitutions against conditional pathogenic microorganisms were studied. In the course of the research, it was found that there is no difference in the humoral parameters of the natural immune status of the organism of Karakul sheep against conditional pathogenic microorganisms, but in terms of the number of immunoglobulins M and G, especially leukocytes in the blood, Karakul sheep of a fine constitution differed significantly from Karakul sheep of a strong and rough constitutions.